Práticas de cuidado no cotidiano do isolamento domiciliar: um estudo sobre a experiência de pessoas que testaram positivo para a Covid-19 - Galera, Laura de Aro (2021)
This research aims to understand the practices of self-caring and caring of others to prevent the transmission of sars-cov-2 from people who tested positive for covid-19 and were in home isolation. The theoretical framework used was the approach to the analysis of discursive practices, incorporating the notion of multiple realities, in the ontological perspective of Annemarie Mol. To obtain the needed information, fifteen semi-structured interviews were carried out via Skype and/or Google Meets. Then, dialogic maps were used to carry out a detailed analysis, considering that the care here conceived can be understood as four layers coordinated with each other by a common relationship as possible routes of contamination: (1) the manifestation of symptoms from the experience with covid-19, (2) home environment care through reorganization of people's routine, (3) with outsiders and cleaning/disposal and (4) care with the procedures of cleaning and disposal of waste. From these four layers, we found the following research results: the manifestation of physical symptoms or emotional symptoms raised by covid-19, as well as the statements involving work as a locus of contamination, meeting with acquaintances/relatives or those who did not know where had become contaminated. For care within the home, we identified respondents who did not undergo isolation and those who fulfilled isolation, reorganizing people's routine, such as the use of individual rooms and utensils. On the other hand, for isolation related to outsiders, delivery apps or support from friends/family were used to access supermarket/pharmacy items. Finally, sanitation and disposal, involving care with cleaning procedures for products and objects that enter the houses and those that leave the house, for disposal. We identified testimonies from people who maintained the selective collection, from those who did not realize that the garbage could be potentially contaminated, and from those who mixed the various residues in a single bag. The contribution of this study is an attempt to collaborate with possible strategies to fight the pandemic that dialogue with the Brazilian reality and with other studies related to the subject